INNOVATIVE TECHNOLOGIES AND DIGITAL SERVICES (International journal of artificial intelligence, 2026)
Innovative technologies and digital services have become one of the most important factors determining the socio-economic development of modern society. In the context of globalization and the rapid development of the information society, the role of digital transformation processes in increasing the efficiency of economic sectors, improving management systems, modernizing education, developing electronic government, and expanding the service sector is steadily increasing. In Uzbekistan, large-scale reforms aimed at the introduction of digital technologies, the formation of an innovative economy, and the expansion of digital services are being consistently implemented. The development strategy of the “Digital Uzbekistan–2030” program serves as an important foundation for the accelerated implementation of information and communication technologies in all sectors. This scientific article analyzes the theoretical foundations, practical significance, socio-economic impact, and prospects of innovative technologies and digital services. The study also examines the importance of digital technologies in education, healthcare, public administration, financial systems, entrepreneurship, and industrial production. Particular attention is given to the scientific approaches reflected in Uzbek educational and scientific literature regarding innovation processes, digital competencies, information security, artificial intelligence technologies, cloud systems, and electronic platforms. The article substantiates that innovative technologies not only improve production efficiency but also create new forms of social communication, intellectual capital, and digital culture. At the same time, issues such as digital inequality, cybersecurity, lack of qualified personnel, and adaptation to technological changes are scientifically analyzed.